Levde lærerliv Volda-læreren i brevbøker 1930-1995 - Madssen, Kjell-Arild (Kyrkjefag Profil, 2020)
"Students from a number of classes that graduated from the teacher's college in Volda during the 1900s maintained their connection over the years through what they called brevbøker, letters collected in book form. In sturdy, hard-backed notebooks and binders, the classmates kept letters informing each other about their professional and personal lives. The material presented here is from six such 'letter books' written by four classes from the four-year program and two classes from the two-year program that graduated between 1930 and 1949. Some of the students kept the correspondence going for over 50 years. In total, the material amounts to roughly 7000 predomently hand-written pages. The letter books are a fascinating entry route into individual histories and the history of the school, as well as professional development and teacher identity, and they shed light on the type of teacher that came to be known as 'the Volda teacher'. The school's rector at the time was Erling Kristvik, and many of the letter-writers proudly refer to themselves as 'Kristvikers'. The letter books can be viewed as a self-portrait of this generation's teacher. This book is the 38th publication in the series Kyrkjefag Profil."